2001
DOI: 10.1063/1.1368398
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen incorporation effects in Fe(001) thin films

Abstract: Nitrogen incorporates into Fe thin films during reactively sputtered TiN capping layer deposition. The influence that this nitrogen incorporation has both on the structure and magnetic properties is discussed for a series of Fe(001) thin films grown at different temperatures. A higher nitrogen content is accompanied by distortion in the Fe lattice and by reduction in the Fe magnetization saturation as well as in the effective anisotropy constant, K. The reduction of K brings as a consequence lowering in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…In addition it has been observed in magnetic Fe-N that and nitrogen atoms tend to diffuse out even at very low temperatures. [6][7][8] Therefore nanocrystalline iron nitrides have these intrinsic limitations in succeeding as good soft-magnetic alloys.…”
Section: Introductionmentioning
confidence: 99%
“…In addition it has been observed in magnetic Fe-N that and nitrogen atoms tend to diffuse out even at very low temperatures. [6][7][8] Therefore nanocrystalline iron nitrides have these intrinsic limitations in succeeding as good soft-magnetic alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption and dissociation of gas phase molecules on various surfaces has been intensively studied [2,4,6,7,[11][12][13][14][15]. Dahl et al [12] studied the molecular dissociation of nitrogen on Ru(0001) surface and showed that it lowered the energy barrier for the molecular dissociation of nitrogen significantly.…”
Section: Introductionmentioning
confidence: 99%
“…A proper understanding of the stability and nitride formation requires knowledge of both Fe and N self-diffusion at atomic length scales. Although the diffusion processes in magnetic bcc-iron nitrides have been discussed, 21,29,30 the diffusion coefficients for Fe and N selfdiffusion in nonmagnetic Fe-N have not been quantified. Conventional techniques for measuring self-diffusion (e.g., secondary ion mass spectroscopy, radioactive tracers, etc.)…”
Section: Introductionmentioning
confidence: 99%